Spectrophotomitric Determination of Tellurium(IV) with 2-Mercaptoethanol - Aziz Ramadan, Abdul; Mandil, Hasna; Kattan, Ghofran (Asian Journal of Chemistry, 2010)
The reaction of Te(IV) with 2-mercaptoethanol (L) can form a complex with the formula Te:L4 in present Britton-Robinson buffer of pH 2. The complex is soluble in water and shows maximum absorption at 241 nm and this was used as the basis for the spectrophotometric determination of Te(IV). Beer's law is obeyed over the concentration range 1.0-200.0 μM of Te(IV). The molar absorptivity of the complex is 6918 L mol-1 cm-1, formation time is 20 min and the working temperature is 50 ºC. The relative standard deviation (RSD %) did not exceed ± 4.1 %.